ANALISIS HUBUNGAN PELAYANAN OPTIMAL DENGAN KEPUASAN PELANGGAN PADA PT PEGADAIAN CP SUKOHARJO - Febrianto Prabowo; Zandra Dwanita Widodo; Abdullah Zailani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this research was to test and measure the relationship and influence both partially and simultaneously on service responsiveness, transaction speed, service presence, professionalism, and overall service satisfaction on customer satisfaction at PT Pegadaian CP Sukoharjo. Then to find out the most dominant variable relationship and its influence on customer satisfaction at PT Pegadaian CP Sukoharjo. This research uses quantitative methods by collecting primary and secondary data through distributing questionnaires and literature data. The population in the customer research at PT Pegadaian CP Sukoharjo took a sample of 50 respondents with Convenience Sampling. Providing good service is something that is expected by every service provider and those who receive service. If a service company is not careful in attracting consumers, it can result in consumers leaving the company and moving to other companies that are considered more satisfying to their customers. In an effort to attract consumers, service companies must further improve their services both in service quality, service results and matters related to the service directly. The results of the study found that both partially and simultaneously there is a significant positive relationship and influence of optimal service quality consisting of service responsiveness, transaction speed, service presence, professionalism, and overall service satisfaction on customer satisfaction at PT Pegadaian CP Sukoharjo. Then it was also found that service responsiveness had the most dominant influence on customer satisfaction at PT Pegadaian CP Sukoharjo. Customer/consumer satisfaction can be explained by service responsiveness, transaction speed, service presence, professionalism, and overall service satisfaction of 85.70. While the remaining 14.30% is explained by other variables outside of this study.